Synthesis and structural characterization of copper(II) coordination polymers with 1,1,2,2-tetra(pyrazol-1-yl)ethane; Inorganic Chemistry Communications; Vol. 64 - Semitut E. Yu. Evgeny Yurjevich; Komarov V. Yu. Vladislav Yu.; Filatov E. Yu. Evgeny Yu.; Kuznetsova A. S. Anastasiya Sergeevna; Khlebnikov A. I. Andrey Ivanovich; Potapov A. S. Andrey Sergeevich (2016, 2016)
Title screen